ANALYZE TURN TAKING IN TALK SHOW ABOUT EDUCATION FOR EVERYONE ON CHANNEL YOUTUBE - Deri Setiawan; Zely Mustika Ningtyas; Ida Lisdawati (PROJECT (Professional Journal of English Education), 2019)
AbstractThe research about speaking language section of discrouse analysis turn taking analyze language. In this research, the researchers use qualitative method and the data is obtained from the video talkshow in the youtube about “Learn English with Taylor Swift”. In the talkshow, there are two persons that have in video, one speaker and one hearer, and tells about someone using social media, trips to Asia, and tour. The talkshow has a message of education, motivation for people to use social media. The purpose of this study is to find out the talkshow had a turn to speak. Analyze in video is the main activity in this research. In the video talkshow the speaker gives questions according to the topics that are brought or presented. In this talkshow the speaker ended the event with the closing. Keywords: Turn taking, talkshow , discourse analysis, qualitative.